PEMBERDAYAAN MASYARAKAT DESA MARU PULAU PURA MELALUI PENGOLAHAN POTENSI LOKAL JAGUNG DAN IKAN TALI DALAM PROGRAM KBPM UNTRIB 2025 - Delila Tanaem (JOURNAL OF COMMUNITY DEDICATION, 2025)
The 2025 Community Empowerment Joint Lecture (KBPM) of Tribuana Kalabahi University in Maru Village, Pura Island, was held with the aim of increasing community economic independence through the utilisation of local potential. The method used was a participatory action approach involving housewives, fishermen, students, field assistants (DPL), and the village government. The results of the activity showed the creation of two innovative flagship products, namely Butter Sweet (Bungaa corn product) and Sambal Ikan Tali, which were produced using modern techniques, packaged hygienically, and began to be introduced through digital platforms. In addition to producing value-added products, this programme also encouraged active community participation, improved technical skills, and fostered confidence to introduce products to a wider market. The conclusion of this activity is that the synergy between academics, the community, and the village government is capable of bringing about sustainable empowerment based on local potential. The success of KBPM in Maru Village is a model of collaboration that can be replicated in other villages in order to strengthen local identity while opening up economic opportunities for the community in the era of the global market.